Preliminary Phase: High Order Thinking Skills-Oriented Student Worksheets in Biology Subjects for Tenth-Grade Students - Maharani, Indah; Fitri, Rahmadhani; Fadhilla, Muhyiatul; Selaras, Ganda Hijrah (Thinking Skills and Creativity Journal, 2022)
The 21st-century learning paradigm confronts students with various challenges. Students are required to be able to think at a higher level to face the challenges of the 21st century. Higher order thinking skills are divided into critical, problem-solving, and creative thinking. One learning media that can hone students' higher-order thinking skills is student worksheets. This study aims to produce student worksheets oriented to higher-order thinking skills to improve higher-order thinking skills for first semester X grade students. This type of research is development research using a 4D model. The subjects of this study were 62 students of class X in the first semester and one biology teacher. This research is limited to analyzing the school's needs for developing LKPD, which is oriented towards higher order thinking skills in the first semester of biology class X. This study uses a survey technique. The results showed that LKPD oriented to higher order thinking skills needs to be developed to train critical thinking skills, problem-solving and creative thinking.